Analisis Akibat Hukum Terhadap Kelalaian Pilot Dalam Menjaga Keselamatan Penerbangan (Kasus Pesawat Batik Air Tahun 2024) - Reinard Christian Yohanes; Amad Sudiro (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Flight safety is a cornerstone of the aviation industry, heavily reliant on the professionalism and vigilance of pilots. This study examines the legal consequences of pilot negligence in maintaining flight safety, focusing on a case involving a fatigued Batik Air pilot. Employing a normative juridical approach, this research analyzes relevant legal frameworks, including Indonesia’s Law No. 1 of 2009 on Aviation, Civil Aviation Safety Regulations (CASR), International Civil Aviation Organization (ICAO) Annex 13, and related legal instruments. The findings reveal that negligence resulting from fatigue constitutes a severe violation of safety standards, breaching the duty of care expected in aviation operations. Such negligence may attract various legal repercussions, ranging from administrative sanctions, such as license revocation, to criminal charges as stipulated under Artt. 411 and 412 of Law No. 1 of 2009. Additionally, airlines may face civil liabilities for compensating passengers for damages incurred. The study also highlights the legal obligation of airlines to ensure the physical and mental fitness of pilots through stringent monitoring of work schedules and regular health evaluations. This paper concludes that strict law enforcement and the establishment of a robust safety culture within the aviation industry are essential to mitigating risks associated with human factors, particularly pilot negligence.